Molecular docking of ferulic acid, bakuchiol and niazirin on peroxisome proliferator-activated receptor gamma (PPAR-γ) as anti-diabetic agents - Anjar Hermadi Saputro; Riri Fauziyya; Sarmoko; Iwan Syahjoko Saputra (Acta Biochimica Indonesiana)
Background: Diabetes mellitus remains one of the most dangerous illnesses worldwide. The PPAR-gamma protein plays a crucial role in lipid and carbohydrate metabolism, making it a key target for diabetes therapy. Research into plant-derived active compounds for diabetes treatment is increasingly important.